ACMF THE PLATFORM TO STRENGTHEN CULTURAL NETWORKS FOR THE FUTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 2 April 2016 – The ASEAN Cultural Music Festival (ACMF) 2016 was held recently at the Dewan Budaya, Universiti Sains Malaysia (USM) and was officiated by the USM Deputy ViceChancellor (Industry and Community Network) Professor Dato’ Dr. See Ching Mey.